2017 HIV Medicine Association of Infectious Diseases Society of America Clinical Practice Guideline for the Management of Chronic Pain in Patients Living With Human Immunodeficiency Virus. (30th October 2017) - Bruce, R Douglas; Merlin, Jessica; Lum, Paula J; Ahmed, Ebtesam; Alexander, Carla; Corbett, Amanda H; Foley, Kathleen; Leonard, Kate; Treisman, Glenn Jordan; Selwyn, Peter
Abstract : Summarized below are the recommendations made in the new guidelines for chronic pain in patients living with human immunodeficiency virus. The panel followed a process used in the development of other Infectious Diseases Society of America (IDSA) guidelines that included a systematic weighting of the strength of recommendation and quality of evidence using the GRADE (grading of recommendations assessment, development, and evaluation) system (Figure 1) [1–5 ]. A detailed description of the methods, background, and evidence summaries that support each recommendation can be found in the full text of the guidelines. Abstract: Pain has always been an important part of human immunodeficiency virus (HIV) disease and its experience for patients. In this guideline, we review the types of chronic pain commonly seen among persons living with HIV (PLWH) and review the limited evidence base for treatment of chronic noncancer pain in this population. We also review the management of chronic pain in special populations of PLWH, including persons with substance use and mental health disorders. Finally, a general review of possible pharmacokinetic interactions is included to assist the HIV clinician in the treatment of chronic pain in this population. It is important to realize that guidelines cannot always account for individual variation among patients. They are not intended to supplant physician judgment with respect to particular patients or special clinical situations. The Infectious Diseases Society of American considers adherence to these guidelines to be voluntary, with the ultimate determination regarding their application to be made by the physician in the light of each patient's individual circumstances.